The Real Effects of the Bank Lending Channel - Gabriel Jiménez; Atif Mian; José-Luis Peydró; Jesuś Saurina (Journal of Monetary Economics, 2020)
We study bank credit booms, exploiting the Spanish matched credit register over 2001-2009. We extend Khwaja and Mian (2008)'s loan-level estimator by incorporating firm-level general equilibrium adjustments. Higher ex-ante bank real-estate exposure increases credit supply to non-real-estate firms, but effects are neutralized by firm-level adjustments for firms with existing banking relationships. However, higher bank real-estate exposure increases risk-taking, by relaxing standards of existing borrowers (cheaper, longer-term and less collateralized credit), and by expanding credit on the extensive margin to first-time borrowers that default substantially more. Results suggest that the mechanism at work is greater liquidity via securitization of real-estate assets
Keywords: E32; E44; G01; G21; G28; 330; bank lending channel; real effects of credit; credit supply booms; real estate; securitization